PENGARUH MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. PERUM PEGADAIAN SALAMA CABANG BIMA - Rahayu, Ningrum; Aprianti, kartin (Universitas Slamet Riyadi, 2020)
This study aims to determine whether there is a significant effect of work motivation on employee job satisfaction at PT. Perum pawnshop salama bima branch. This research is an associative type by explaining using a quantitative approach, assisted by using the SPSS version 21 statistical program. Data collection techniques in this study use observation, interviews, questionnaires and literature study. The population of this study uses employees at PT. Perum pawnshop Salama Bima branch as many as 40 people. The sampling technique used was simple random sampling technique, in order to obtain a sample of 36 employee respondents at PT. Perum pawnshop salama bima branch, which has the status of permanent and honorary employees. The data analysis techniques used were validity and reliability tests, simple linear regression analysis, dermination and t test. In this study the coefficient of determination shows that the assessment of motivation is influenced by employee job satisfaction of 72.0% while the remaining 28.0% is influenced by other factors not referred to in this study, while the t test value is 9.341 and the Sig. 0,000 will then be compared with the provisions if Sig <0.05 then it is stated that there is an influence between variable X and variable Y and if sig. > 0.05, it is stated that there is no influence. The sig value of the SPSS output of 0,000 is actually smaller than 0.05 (Sig. 0.00 <0.05), so it is stated that there is a significant influence of work motivation on job satisfaction.